1981
DOI: 10.1111/j.1476-5381.1981.tb10427.x
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Ouabain Uptake in Isolated Myocardial Cells: Dependence on Extracellular Potassium and Calcium Concentration

Abstract: Spontaneously beating myocardial cells isolated from newborn rats have been used to evaluate the time course of cellular ouabain uptake. The rate of cellular uptake and the amount of ouabain bound at equilibrium were computed by fitting the experimental data to the conventional exponential equation for receptor binding of drugs. At normal extracellular potassium and calcium concentrations a biexponential equation was the best fit to the experimental data, indicating two receptor sites of ouabain with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Low S K levels affect myocardial resting membrane potential, which increases the probability of ventricular arrhythmias and sudden cardiac death (11). Hypokalemia can also predispose patients to developing diastolic dysfunction, digoxin toxicity, and insulin resistance, all of which increase the risk for cardiovascular events and death (12)(13)(14)(15)(16). Dietary potassium depletion has been linked to the genesis of hypertension, and supplementation can improve BP control (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Low S K levels affect myocardial resting membrane potential, which increases the probability of ventricular arrhythmias and sudden cardiac death (11). Hypokalemia can also predispose patients to developing diastolic dysfunction, digoxin toxicity, and insulin resistance, all of which increase the risk for cardiovascular events and death (12)(13)(14)(15)(16). Dietary potassium depletion has been linked to the genesis of hypertension, and supplementation can improve BP control (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…It shortened in excess Ca and K-containing solution. An is known that Ca activates the neuronal Na,K-ATPase unexpected observation was made in the rabbit pul- , decreases internal Na activity monary artery, namely that excess K failed to antagalready elevated by Na-pump inhibition (Deitmer & (Meldgaard et al, 1981) and further delays the tion, the cardiac glycoside was applied together with ouabain-evoked rise of the miniature endplate poten-excess Ca (Figure 4). The rate of release did not differ tial (Baker & Crawford, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Baker & Crawford (1975) have shown that external Ca removal shortens the initial delay of ouabain-evoked acetylcholine release from the motor nerve terminal. In Na-pump inhibited Purkinje fibres, excess Ca decreased the internal Na activity (Deitmer & Ellis, 1978) and in myocardial cells excess Ca inhibited both the binding and uptake of ouabain (Meldgaard et al, 1981). Furthermore Powis et al (1983) have shown that Ca stimulates the neuronal Na,K-ATPase.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments carried out in the 1970s and 1980s demonstrated that hypokalemia enhances digoxin toxicity by at least two mechanisms: increased cardiac glycoside binding to Na ϩ -K ϩ -ATPase, and reduced renal clearance of digitalis glycosides due to increased proximal tubule reabsorption [17][18][19].…”
Section: How Do Abnormal Serum Potassium Levels Affect the Toxicity Omentioning
confidence: 99%